The Differential Efficacy of a Professional Development Model on Reading Outcomes for Students With and Without Disabilities. (July 2021) - Swanson, Elizabeth; Vaughn, Sharon; Fall, Anna-Maria; Stevens, Elizabeth A.; Stewart, Alicia A.; Capin, Philip; Roberts, Greg
This study examined the differential effects of Strategies for Reading Informational Text and Vocabulary Effectively (STRIVE) on the vocabulary, reading comprehension, and content learning among 4, 757 fourth-grade students with and without disabilities. Schools were assigned to one of three conditions: researcher-supported professional development (RPD), school-supported professional development (SPD), or business as usual (BAU). Treatment teachers received 12 hr of professional development distributed over time and delivered a set of instructional practices for teaching vocabulary and comprehension embedded within 36 social studies lessons (45 min per lesson). Findings revealed that students with and without disabilities in classes assigned to STRIVE treatment (SPD and RPD) outperformed their peers in classes assigned to the BAU condition at a statistically significant level on measures of content knowledge and content vocabulary and a distal measure of vocabulary. STRIVE did not affect students with disabilities (SWDs) and without disabilities differentially on the measures of content knowledge and distal vocabulary, though effects sizes for non-SWDs in SPD and RPD were larger than those for SWDs.